A Comparative Analysis of Immigration Laws: Case Studies of the Canada, Germany, the United States of America (USA) and the United Kingdom (UK) - Siddiqui, Rawaid Hussain (International Journal of Law Analytics, 2024)
This research paper presents a comparative analysis of immigration laws across four countries: Canada, Germany, the UK and the USA. Through an examination of historical contexts, legal frameworks, policy objectives, and integration efforts, the study explores the complexities of immigration governance in diverse socio-political contexts. Utilizing a combination of primary sources, including government documents and legislative records, and secondary sources such as scholarly articles and reports, the analysis sheds light on the evolution of immigration policies and practices in each country. By employing a structured comparative framework, the paper identifies commonalities and differences, discerns emerging trends, and evaluates the effectiveness of various approaches to immigration management. Furthermore, the study underscores the significance of cross-national learning and knowledge exchange in shaping evidence-based policymaking and addressing contemporary challenges in immigration governance. Ultimately, this research contributes to a deeper understanding of immigration dynamics and informs policymakers, scholars, and practitioners on strategies for enhancing the efficacy and inclusivity of immigration policies in a globalized world.